MEDIA PEMBELAJARAN ALA NABI (Kajian Living Hadis Riwayat Muslim Bab Birrun No. 149) - Arbain Nurdin (Piwulang: Jurnal Pendidikan Agama Islam, 2020)
This article describes two research focuses namely how the value of instructional media in the Muslim history hadith chapter Birrun No. 149 and how to understand the meaning of the hadith and the practice of students as teachers of the practices of the Study Program of Hadith Science the Faculty of Usuluddin, Adab and Humanities of IAIN Jember. And the result is the value of learning media in the hadith is textually found in the word ashabi'u which means fingers. While students understand that the tradition of text has a textual discussion of how the task of parents to educate and take care of their daughters until they are adults, then practice students after understanding the meaning of the hadith contextually that is when becoming a teacher practice always and often use the media fingers in learning AbstrakArtikel ini mendeskripsikan dua fokus penelitian yaitu bagaimana nilai media pembelajaran di dalam hadis riwayat Muslim bab birrun No. 149 dan bagaimana pemahaman makna hadis tersebut serta pengamalan mahasiswa selaku guru praktikan dari prodi Ilmu Hadis Fakultas Ushuluddin, Adab dan Humaniora IAIN Jember. Dan hasilnya adalah nilai media pembelajaran di dalam hadis tersebut secara tekstual ditemukan pada kata ashabi’u yang bermakna jari jemari. Sedangkan mahasiswa memahami bahwa matan hadis tersebut secara tekstual membahas tentang bagaimana tugas orang tua untuk mendidik dan menjaga anak-anak perempuannya hingga mereka dewasa, lalu pengamalan mahasiswa setelah memahami makna hadis tersebut secara kontekstual yaitu saat menjadi guru praktikan selalu dan sering menggunakan media jari jemari dalam pembelajaran.